REVIEW OF ONTOLOGY ALGINMENT SYSTEMS - Alhassan, B.B; Jauro, F; Musa, I.M (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2018)
Ontologies were developed to describe a given domain in the semantic web. However due to variation in views of developers, ontologies are heterogeneous hence preventing interoperability. Ontology alignment solves this heterogeneity problem by discovering relationships between entities of different ontologies. Various ontology alignment systems have been developed over the years. Different researches have been carried out in an attempt to review this area. However, there is still a need for an up to date review of the ontology alignment systems in order to allow continuous research in the field. In this paper, twelve different ontology alignment systems were reviewed nine were found to be fully automatic while three are semi-automatic. Furthermore most of the systems use a combination of different matching techniques while others use only single matching technique.